Correlation between disc damage likelihood scale and vertical cup disc ratio with Automated Humphrey Perimetry in glaucoma patients attending a tertiary care hospital, Kathmandu, Nepal - Singh, Pranisha; Rijal, Aditya Prasad (Nepal Medical College Journal, 2022)
Glaucoma is the second leading ocular disease of irreversible blindness. Glaucoma is a progressive disorder and requires serial evaluation in order to monitor disease progression and optimize therapy. The objective of this study was to determine the correlation between disc damage likelihood scale (DDLS) and vertical cup disc ratio (VCDR) with the results of Humphrey field analyzer (HFA) parameters. This study was a descriptive, cross-sectional and observational study. A total of 104 eyes of 52 patients diagnosed with primary open angle glaucoma or normal tension glaucoma were examined. DDLS staging, VCDR and HFA 24-2 visual fields were obtained from the patients. The correlation of DDLS and VCDR with Mean deviation (MD), Pattern standard deviation (PSD) and Glaucoma hemi field test (GHT) of HFA was calculated by Pearson correlation coefficient (r). DDLS showed a coefficient correlation value of r = -.628, r = .391 and r = .395 (p = <0.000) when correlated against HFA MD, PSD and GHT respectively. VCDR showed a coefficient correlation value of r = -.524, r = .317 and r = .221 when correlated against HFA MD, PSD and GHT respectively. DDLS has a better correlation compared to VCDR with all the parameters.